Acroangiodermatitis or pseudo-Kaposi's sarcoma: a challenging diagnosis - Hanan Ragragui; Ouasmin; Soraya Aouali; Nada Zizi; Siham Dikhaye (Our Dermatology Online, 2021)
Acroangiodermatitis (AAD), also referred to as pseudo-Kaposi's sarcoma, is a vascular-proliferative disease characterized by reactive proliferation of small blood vessels in response to congenital or acquired vascular lesions. There are mainly two clinical variants of acroangiodermatitis; STEWART-BLUEFARB syndrome and the Malian type. There is clinical and histological similarity with Kaposi's sarcoma hence the interest of immunohistochemical analysis. We report the case of a 40-year-old man with cutaneous lesions localized on the lower limbs. Clinical, dermoscopic, histological and immunohistochemical investigation led to a diagnosis of Kaposi-like acroangiodermatitis.